2020
DOI: 10.3892/ijo.2020.5041
|View full text |Cite
|
Sign up to set email alerts
|

G6PD facilitates clear cell renal cell carcinoma invasion by enhancing MMP2 expression through ROS‑MAPK axis pathway

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) is crucial rate-limiting enzyme of the pentose phosphate pathway (PPP). G6PD dysregulation has been reported in various types of human cancer, and the role of G6PD in cancer progression was demonstrated in numerous studies. A previous study from our laboratory described the prognostic significance of G6PD in clear cell renal cell carcinoma (ccRCC), and demonstrated its proliferative role through positive feedback regulation of the phosphorylated form of signal transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 63 publications
4
38
1
Order By: Relevance
“…ROS interacts with numerous oncogenic signaling pathways, such as the STAT3 and MAPK pathways, to favor the development of human cancers. Moreover, proliferation and metastasis related genes, such as cyclins and MMPs, were found to be involved in this mechanisms of action [9,12]. These implies that ROS might be involved in the G6PDmediated upregulation of Cyclin E1 and MMP9 in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…ROS interacts with numerous oncogenic signaling pathways, such as the STAT3 and MAPK pathways, to favor the development of human cancers. Moreover, proliferation and metastasis related genes, such as cyclins and MMPs, were found to be involved in this mechanisms of action [9,12]. These implies that ROS might be involved in the G6PDmediated upregulation of Cyclin E1 and MMP9 in our study.…”
Section: Discussionsupporting
confidence: 55%
“…When most of the cell fell off, fresh culture medium containing serum was added and transferred to new culture bottles by 1:3. G6PD-overexpressing or G6PD-knocked down stable cells establishment were conducted as described before [9,12]. h. Cells were harvested and cell cycle analysis were performed as described in a previous report by a PARTEC CyFlow Space flow cytometer and ModFit software [12].…”
Section: Cell Culture and Stable Cell Constructionmentioning
confidence: 99%
“…Previous studies from our laboratory demonstrated that G6PD overexpression lead to the increment of G6PD-NADPH-NOX4-dependent ROS accumulation and then pSTAT3 and MAKP signaling over-activation in ccRCC [19,20]. However, several problems, such as alterations in ROS-triggered signaling pathways or other relevant regulators responsible for G6PD high expression, remained to be clarified.…”
Section: Discussionmentioning
confidence: 92%
“…A further investigation descripted that the overexpressed G6PD positively regulated reactive oxygen species (ROS) generation by facilitating NADPH oxidase 4 activity, increased phosphorylated signal transducer and activator of transcription 3 (pSTAT3) activation and enhanced RCC development [19]. Moreover, G6PD could stimulate ccRCC invasion through facilitating ROS-MAPK-MMP2 axis pathway [20]. The aforementioned results suggested that how G6PD regulated the downstream target, influenced ROS production, and promoted RCC growth and invasion had partially been revealed, but why G6PD was aberrantly overexpressed during ccRCC tumorigenesis was still not completely known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory demonstrated that G6PD overexpression lead to the increment of G6PD-NADPH-NOX4-dependent ROS accumulation and then pSTAT3 and MAKP signaling over-activation in ccRCC [19,20]. However, several problems, such as alterations in ROS-triggered signaling pathways or other relevant regulators responsible for G6PD high expression, remained to be clari ed.…”
Section: Discussionmentioning
confidence: 92%